NATION-BUILDING CONFESSIONS: CARCERAL MEMORY IN POSTGENOCIDE RWANDA - Baldwin, Gretchen (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2019)
The postconflict Rwandan state has crafted a “we are all Rwandans” national identity narrative without ethnicity, in the interest of maintaining a delicate, postgenocide peace. The annual genocide commemoration period called Kwibuka—“to remember”—which takes place over the course of one hundred days every year, is an underresearched part of this narrative. During the commemoration period, génocidaires’ confessions increase dramatically; these confessions lead the government to previously undiscovered graves all over the country, just as confessions given during the grassroots justice system—gacaca—did in the more immediate aftermath of the genocide. According to a prominent government official known for his prison outreach, the Rwandan government no longer provides incentives for prisoners to confess. Instead, he stated in a 2017 interview, those who speak up over twenty years later are simply “moved by the spirit of Kwibuka.” When confessions are made, memories of past action (“bad behaviour”) are used by the state, seemingly toward an ultimate end of reinforcing the national master narrative, to subsume the individual memories of innocent survivors into the national collective memory. This paper explores the questions around the state’s evolving use of prisoner confessions, both how those confessions are obtained, and how they factor into commemoration practices now.